An Analysis of Affixation Processes of Derivation and Inflection in Article with the Title “The Government of the Republic of Indonesia” - Made Prima Devi Hutaminingrum (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study aims to analyze the derivational and inflection affixation processes in the article entitled